4D printed programmable auxetic metamaterials with shape memory effects. (1st January 2022) - Wan, Mengqi; Yu, Keqin; Sun, Huiyu
Abstract: Auxetic metamaterials, which expand transversely when longitudinally stretched, are widely used in engineering fields, such as flexible electronics and biomedicine. However, they have fixed configurations and properties without the ability to tune and adapt after fabrication. In this paper, we propose three kinds of 4D printed programmable metamaterials (triangular, square and honeycomb lattice metamaterials). The mechanical properties of the designed metamaterials for different topological angle θ and radius R are studied through experiments and finite element analysis (FEA). Results show that the triangular and square lattice metamaterials achieve large deformation and auxetic behaviors, and due to shape memory effects, the Poisson's ratios and the elastic moduli of the metamaterials can be programmed by tuning the topological parameters and temperature. Furthermore, the proposed cylindrical shells with desired mechanical properties and configurations demonstrate potential applications in biomedical scaffolds.